Is It Necessary to Include Promise in a Deed of Granting of Mortgage Rights? - Zuhir, Mada Apriandi; Yahanan, Annalisa; Murzal, Murzal (Jurnal Penelitian Hukum De Jure, 2024)
To secure the funds that have been granted to the debtor, in loan agreement between creditor and debtor, a guarantee agreement is usually included. One form of collaterals that is most in demand is land collateral. This research aims to analyze funds security that has been handed over to debtors in connection with loan agreement and promises (clauses) inclusion in a Deed of Granting of Mortgage Rights. This normative research uses statutory, conceptual and interpretive approaches. This study examines several deeds to search and analyze the promises (clauses) in the guarantee agreement. The result shows that the loan agreement includes a promise to provide collateral that will be attached with mortgage rights, to secure the credit that has been given to the debtor as security for repayment of credit loan. Therefore, the loan agreement contains rights and obligations of parties as a form of prudential principles. Furthermore, a Deed of granting of mortgage rights considerably needs to include promises (clauses) as a manifestation of conditions related to the guarantee provided. In its regulation (Mortgage Rights Law), these promises are optional (not mandatory) being included in a Deed of granting of mortgage rights. However, in practice these promises are always included in a deed at the creditor’s request, with the aim being a kind of self-protection to creditor. However, Mortgage Rights Law also provides a balance of protection to debtors, namely promises that are prohibited from being included that creditors can immediately own the object of mortgage rights when the debtor defaults. If such promise is included, then the Deed of Granting of Mortgage Rights is null and void.